2005
DOI: 10.1074/jbc.m411092200
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Human Organic Anion-transporting Polypeptide 1A2 (OATP1A2)

Abstract: Organic anion-transporting polypeptide 1A2 (OATP1A2) is a drug uptake transporter known for broad substrate specificity, including many drugs in clinical use. Therefore, genetic variation in SLCO1A2 may have important implications to the disposition and tissue penetration of substrate drugs. In the present study, we demonstrate OATP1A2 protein expression in human brain capillary and renal distal nephron using immunohistochemistry. We also determined the extent of single nucleotide polymorphisms in SLCO1A2 upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
266
3
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(282 citation statements)
references
References 14 publications
12
266
3
1
Order By: Relevance
“…In this study, SLCO1A2 genotyping was not performed because SNPs that affect OATP1A2 transport activity are not typically found in the Asian population. 46 Consequently, the disposition of IM may be altered by ABCG2 421C4A, such that polymorphism-dependent differences in IM trough concentration reflect a difference in hepatic IM biliary excretion rather than a difference in intestinal IM absorption.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SLCO1A2 genotyping was not performed because SNPs that affect OATP1A2 transport activity are not typically found in the Asian population. 46 Consequently, the disposition of IM may be altered by ABCG2 421C4A, such that polymorphism-dependent differences in IM trough concentration reflect a difference in hepatic IM biliary excretion rather than a difference in intestinal IM absorption.…”
Section: Discussionmentioning
confidence: 99%
“…However, some members show a tissuespecific distribution; OATP1B1 and OATP1B3 are exclusively expressed in liver (Hsiang et al 1999, Konig et al 2000, whereas OATP1C1 is only present in the brain and in the Leydig cells of the testis (Pizzagalli et al 2002). Furthermore, most OATP family members are expressed at the basolateral membrane of polarized cells (Hsiang et al 1999, Konig et al 2000, Lee et al 2005.…”
Section: Oatpsmentioning
confidence: 99%
“…Two common (Ile13Thr and Glu172Asp) and two rare (Arg168Cys and Asn278X) protein-altering variants of OATP1A2 showed altered transport function. In a different study, Glu172Asp and Asn135Ile variants showed markedly reduced transport of the OATP1A2 substrates estrone sulfate (E1S) and deltorphin II (Lee et al 2005). Other variants (Ala187Thr and Thr668Ser) appeared to have substrate-dependent changes in transport activity (Lee et al 2005).…”
Section: Oatp1a2mentioning
confidence: 99%
“…All the intestinal transporters for organic anions are also expressed in human hepatocytes more or less, although ASBT, OATP1A2 and MRP1 appear not to be present in these cells, and little seems to be known about the expression of hepatic MCTs. [50][51][52] However, several additional transporters are expressed in the liver. The majority of these are mainly transporters for organic anions, i.e.…”
Section: Localization In the Enterohepatic Systemmentioning
confidence: 99%
“…Bilirubin [143] Chenodeoxycholate [144] Chlorambuciltaurocholate [145] Dexamethasone [146] Cholate [144] 93 Cholate [144] Ciprofloxacin [147] Ciprofloxacin [147] DHEAS [40,146] 6.6 E217bG [146] Enoxacin [147] Enoxacin [147] E217bG [40,143] Estrone-3-sulfate [146] Fexofenadine [19,148] 6.4 Erythromycin [148] Estrone-3-sulfate [40,51,149] 16/59 3-Iodothyronamine [150] Gatifloxacin [147] Grepafloxacin [147] Glycocholate [40,144] Taurochenodeoxycholate [144,146,149] Imatinib [151] Indinavir [148] Prostaglandin E2 [40] Levofloxacin [147] 136 Ketokenazole [148] Reverse triiodothyronine [38] Taurocholate [144] Lomefloxacin [147] Lovastatin [148] Taurochenodeoxycholate [144] Tauroursodeoxycholate [144,146] Methotrexate [152] 457 Moxifloxacin [147] Taurocholate [40,…”
Section: Oatp1a2 (Oatp-a)mentioning
confidence: 99%